LeFort Colpocleisis: Unmet Expectations about Correction of Urinary Symptoms Are Related to Disappointment and Regret - Themistoklis Mikos; Sofia Tsiapakidou; Matteo Lioupis; Christos Anthoulakis; Iakovos Theodoulidis; Grigoris F. Grimbizis (Wolters Kluwer Medknow Publications, 2024)
Introduction and Hypothesis The aims of this study were to define long-term anatomic outcome, satisfaction rate, and reasons for disappointment and regret in a group of patients with advanced pelvic organ prolapse who underwent LeFort colpocleisis (LFC). Materials and Methods This was a retrospective, single-center, cohort study including consecutive patients who underwent LFC from 2007 to 2021. All patients had surgery involving vaginal hysterectomy and anti-incontinence procedure where clinically indicated. All patients were examined 3 months after surgery. A cross-sectional telephone survey was performed in 2022 using the Patient Global Impression of Severity (PGI-S), Patient Global Impression of Improvement (PGI-I), and Patient Global Impression of Change (PGI-C) questionnaires, as well as the Decision Regret Scale. Student's t-test, Fisher's Chi-square test, and univariable logistic regression analysis were carried out. Results One hundred and forty-one patients (mean age 74.95 ± 6.25 years) were included. The mean preoperative POP Quantification C/D point was +6 (±2.7). In 86 (60.99%) patients, a hysterectomy and in 56 (39.71%), a mid-urethral synthetic sling was performed. At 3-month follow-up, there was one prolapse recurrence (0.71%) and no case of regret of sexual function loss. In the long term, 28 patients died, and 69 patients were interviewed through telephone (follow-up 61.65 months). The mean PGI-S, PGI-I, and PGI-C scores were 1.42 (±0.81), 1.93 (±1.45), and 5.91 (±1.69) respectively, and no patient declared regret about vaginal intercourse loss. Preoperative and postoperative persistent or de novo mixed UI appeared to be related to decreased satisfaction and regret post-LFC (P = 0.0021). Conclusion LFC is a valuable, easy-to-perform technique with long-lasting results and decreased postoperative anti-incontinence rates. However, de novo or persistent urinary incontinence appears to be related to decreased satisfaction rates.